Wavelet-based spectral finite element dynamic analysis for an axially moving Timoshenko beam. (August 2017) - Mokhtari, Ali; Mirdamadi, Hamid Reza; Ghayour, Mostafa
Highlights: Develop a wavelet-based spectral finite element model for a moving Timoshenko beam. Verify the accuracy by comparing its results with those of other methods. Use finite element and spectral finite element method as comparable variants. Investigate effect of beam moving speed and pretension on vibration and stability. Abstract: In this article, wavelet-based spectral finite element (WSFE) model is formulated for time domain and wave domain dynamic analysis of an axially moving Timoshenko beam subjected to axial pretension. The formulation is similar to conventional FFT-based spectral finite element (SFE) model except that Daubechies wavelet basis functions are used for temporal discretization of the governing partial differential equations into a set of ordinary differential equations. The localized nature of Daubechies wavelet basis functions helps to rule out problems of SFE model due to periodicity assumption, especially during inverse Fourier transformation and back to time domain. The high accuracy of WSFE model is then evaluated by comparing its results with those of conventional finite element and SFE results. The effects of moving beam speed and axial tensile force on vibration and wave characteristics, and static and dynamic stabilities of moving beam are investigated.